Identifikasi Pembayaran Bergerak (Mobile Payment) yang Mengganggu (Disruptive) di Indonesia - Robertta Indira Mawarrini (Universitas Muhammadiyah Sidoarjo, 2017)
This research aims to identify disruptive mobile payment in Indonesia. Mobile payment as a sector of financial technology is enabling the lifestyle transformation of electronic banking. The future of retail banking is a smartphone experience that gladden and customers also aspire for a “bank in my pocket”. Mobile payment as the second sector most likely to be disrupted in the intersection of finance and technology industry. The promising approach of disruptive innovations is proposed by Professor Christensen from Harvard Bussiness School. They suggest that two strategies for identifying the new disruptive growth of business, as following: “creating a new market as a base of disruption” and “disrupting the business model from the low end”. Our research findings that mobile payment tends to replicate bank’s business model, its business model only espouse financial institution. Customers also desire their mobile payment have to the following three priorities: anytime and anywhere, fully digital (convenience), fast and accurate. When epicenter of disruption of mobile payment have been widely misunderstood and its basic principle frequently misapplied. Islamic mobile payment should be immediately developed in order to expand the coverage of Islamic financial services